Sistem Pendidikan di Thailand - Astri Azani; Mislaini Mislaini; Sus Rahma Yuni; Sahronia Rambe (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
Thailand, a developing country in Southeast Asia, is striving to enhance its value and position on the world stage through the tourism industry. A country with a majority Buddhist population, Thailand is developing Halal Tourism as a new strategy to attract Muslim travelers.The development of halal tourism in Thailand is driven not only by economic motives but also non-economic considerations. Economically, the Thai government aims to open new destinations and expand the market to meet Muslim tourists' needs. A unique aspect is that Thailand has a minority Muslim population with a history of tension, especially in the Southern region. The government involves Southern Thai communities in halal tourism development, demonstrating efforts to create an inclusive society. This strategy is expected to ease political tensions that have existed due to economic disparities. By involving minority groups in tourism development, the Thai government hopes to achieve long-term peace and improve the country's positive image. The approach represents a strategic attempt to transform potential conflict zones into economic opportunities, using tourism as a tool for social integration and economic development.